Comparison of the biological impact of aerosol of e-vapor device with MESH® technology and cigarette smoke on human bronchial and alveolar cultures. (1st February 2021) - Giralt, Albert; Iskandar, Anita R; Martin, Florian; Moschini, Elisa; Serchi, Tomasso; Kondylis, Athanasios; Marescotti, Diego; Leroy, Patrice; Ortega-Torres, Laura; Majeed, Shoaib; Merg, Celine; Trivedi, Keyur; et al.
Graphical abstract: Highlights: Biological impact of exposure to an aerosol of an e-vapor device was investigated using human bronchial and alveolar models. The biological impact of e-vapor aerosol exposure was lower than that of cigarette smoke at similar nicotine levels. The exposure effects at the molecular levels were evaluated using a systems toxicology approach. Abstract: Exposure to aerosol from electronic vapor (e-vapor) products has been suggested to result in less risk of harm to smokers than cigarette smoke (CS) exposure. Although many studies on e-vapor products have tested the effects of liquid formulations on cell cultures, few have evaluated the effects of aerosolized formulations. We examined the effects of acute exposure to the aerosol of an e-vapor device that uses the MESH ® technology ( IQOS ® MESH, Philip Morris International) and to CS from the 3R4F reference cigarette on human organotypic bronchial epithelial culture and alveolar triculture models. In contrast to 3R4F CS exposure, exposure to the IQOS MESH aerosol (Classic Tobacco flavor) did not cause cytotoxicity in bronchial epithelial cultures or alveolar tricultures despite its greater concentrations of deposited nicotine (3- and 4-fold, respectively). CS exposure caused a marked decrease in the frequency and active area of ciliary beating in bronchial cultures, whereas IQOS MESH aerosol exposure did not. Global mRNA expression and secreted protein profiles revealed a significantly lower impact of IQOS MESH aerosol exposure than 3R4F CS exposure. Overall, our whole aerosol exposure study shows a clearly reduced impact of IQOS MESH aerosol relative to CS in bronchial and alveolar cultures, even at greater nicotine doses.